The Effect Of Growth Opportunity And Company Size On Sustainable Growth Rate In Manufacturing Companies (Manufacturing Company Study Period 2019-2023) - Erawati, Teguh; Hidayaningtyas, Mutiara Nur (Universitas Muhammadiyah Pontianak, 2025)
In a business context, SGR is an important indicator that shows how fast a company can grow without requiring external financing. Sustainable growth is very important for companies to ensure operational continuity and competitiveness in the market. This study aims to test the effect of growth opportunities and company size on sustainable growth rates in manufacturing companies for the period 2019-2023. Secondary data obtained from published company financial reports were used as main data. This research uses quantitative methods with multiple linear regression analysis to determine the influence of independent variables on the dependent variable. The research results show that growth opportunity has a positive and significant effect on the sustainable growth rate. Apart from that, company size as an intervening variable also has a significant effect in strengthening the relationship between growth opportunity and sustainable growth rate. This research provides an important contribution to company management in formulating appropriate strategies to increase sustainable growth in all sectors in manufacturing companies.